2011
DOI: 10.1007/s10072-011-0761-7
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological and behavioral characterization of the saphenous chronic constriction injury model of neuropathic pain in rats

Abstract: The aim of the present study was to develop a new experimental pain model by adapting the chronic constriction injury (CCI) model of the sciatic nerve to the exclusively sensory saphenous nerve in rats. Animals were divided into naïve, sham, and two experimental groups, in which two or four 4-0 chromic gut ligatures were loosely ligated around the saphenous nerve. Then, behavioral signs of neuropathic pain were observed for 8 weeks. In rats with four ligatures, prominent mechanical allodynia and thermal hypera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 43 publications
1
5
0
Order By: Relevance
“…In this study, seven days after CCI, the mice showed a relatively high degree of similarity to other studies published on neuropathic pain in terms of the degrees of allodynia and hyperalgesia, demonstrated by the increased responsiveness to von Frey filaments, cold-plate and plantar test apparatus. Unilateral sciatic nerve ligation induced significant behavioral alterations resulting in ipsilateral mechanical allodynia appearing on the 7th day of the surgery; our results are in accord with Gunduz et al (2011). The cold allodynia induced by CCI peaked on the 7th postoperative day and this is consistent with Tanimoto-Mori et al (2008) and thermal hyperalgesia that was expressed with latency, on the 7th day after operation.…”
Section: Discussionsupporting
confidence: 80%
“…In this study, seven days after CCI, the mice showed a relatively high degree of similarity to other studies published on neuropathic pain in terms of the degrees of allodynia and hyperalgesia, demonstrated by the increased responsiveness to von Frey filaments, cold-plate and plantar test apparatus. Unilateral sciatic nerve ligation induced significant behavioral alterations resulting in ipsilateral mechanical allodynia appearing on the 7th day of the surgery; our results are in accord with Gunduz et al (2011). The cold allodynia induced by CCI peaked on the 7th postoperative day and this is consistent with Tanimoto-Mori et al (2008) and thermal hyperalgesia that was expressed with latency, on the 7th day after operation.…”
Section: Discussionsupporting
confidence: 80%
“…For instance, the anti-nociceptive and anti-allodynic effectiveness of GBP has been widely supported by studies in animal models of many types of pain induced by peripheral nerve injury such as spinal nerve ligation [47][48][49][50], chronic compression injury [51][52][53][54][55][56] and spared nerve injury [57,58]. Moreover, GBP has also been demonstrated to have anti-allodynic and anti-hyperalgesic effects in animal models of diabetic neuropathy [29] and postherpetic neuralgia [59].…”
Section: Gabapentinoid Insensitivity In Central Neuropathic Pain Of Tmentioning
confidence: 99%
“…Even most of the powerful painkillers like morphine and other opioid drugs are inadequate; they are generally effective at higher doses when their adverse effects are seen. In general, antidepressants (e. g., amitriptyline and nortriptyline) and some anticonvulsant drugs (e. g., gabapentin, pregabalin) are recommended for first-line treatment of neuropathic pain; however, it is clear that there is a lack of specific medications that effectively treat this indication [5][6][7].…”
Section: Introductionmentioning
confidence: 99%